Synthesis and crystal structure of diisothiocyanatotetrakis(4-methylpyridine N-oxide)cobalt(II) and diisothiocyanatotris(4-methylpyridine N-oxide)cobalt(II) showing two different metal coordination polyhedra - Christian Näther; Inke Jess (Acta Crystallographica Section E: Crystallographic Communications, 2024)
The reaction of Co(NCS)2 with 4-methylpyridine N-oxide (C6H7NO) leads to the formation of two compounds, namely, tetrakis(4-methylpyridine N-oxide-κO)bis(thiocyanato-κN)cobalt(II), [Co(NCS)2(C6H7NO)4] (1), and tris(4-methylpyridine N-oxide-κO)bis(thiocyanato-κN)cobalt(II), [Co(NCS)2(C6H7NO)3] (2). The asymmetric unit of 1 consists of one CoII cation located on a centre of inversion, as well as one thiocyanate anion and two 4-methylpyridine N-oxide coligands in general positions. The CoII cations are octahedrally coordinated by two terminal N-bonding thiocyanate anions in trans positions and four 4-methylpyridine N-oxide ligands. In the extended structure, these complexes are linked by C—H...O and C—H...S interactions. In compound 2, two crystallographically independent complexes are present, which occupy general positions. In each of these complexes, the CoII cations are coordinated in a trigonal–bipyramidal manner by two terminal N-bonding thiocyanate anions in axial positions and by three 4-methylpyridine N-oxide ligands in equatorial positions. In the crystal, these complex molecules are linked by C—H...S interactions. For compound 2, a nonmerohedral twin refinement was performed. Powder X-ray diffraction (PXRD) reveals that 2 was nearly obtained as a pure phase, which is not possible for compound 1. Differential thermoanalysis and thermogravimetry data (DTA–TG) show that compound 2 start to decompose at about 518 K.